1997
DOI: 10.1021/bi9707133
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Helix Induction by Trifluoroethanol:  A Framework for Extrapolating the Helix-Forming Properties of Peptides from Trifluoroethanol/Water Mixtures Back to Water

Abstract: To establish a framework for extrapolating the helix-forming properties of peptides from TFE/H2O mixtures (TFE = 2,2, 2-trifluoroethanol) back to water, the thermal unfolding curves have been measured by circular dichroism for four repeating-sequence peptides, with chain lengths from 7 to 22 residues. The unfolding curves were measured between 0 and 50 volume percent TFE and were fitted to the modified Lifson-Roig theory. A single set of helix-coil parameters fits the results for the four peptides at each TFE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

53
660
5
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 668 publications
(731 citation statements)
references
References 39 publications
53
660
5
4
Order By: Relevance
“…22 The 1974 Chen equation for calculating percent helix values was later tested with Ala-based peptides of varying chain lengths and was refined slightly. 26 In the case of the E4K4 peptide, the helix content is high at 59%, close to the value predicted by the AGADIR algorithm (Table I). …”
Section: Resultssupporting
confidence: 81%
“…22 The 1974 Chen equation for calculating percent helix values was later tested with Ala-based peptides of varying chain lengths and was refined slightly. 26 In the case of the E4K4 peptide, the helix content is high at 59%, close to the value predicted by the AGADIR algorithm (Table I). …”
Section: Resultssupporting
confidence: 81%
“…Thus deprotection of the alanine dipeptide Boc-Ala 2 - 20 OMe or tripeptide Boc-Ala 3 -OMe at the C-terminus using LiOH followed by careful neutralisation and subsequent coupling to the free amine 2 yielded the oligopeptides 3a-b. Even though both routes gave the desired oligopeptides 3 in the same number of steps, route B presents the significant advantage to be convergent 25 rather than a completely linear reaction sequence. The imidazole ring was then alkylated by gently heating 3 with MeI in MeCN to give the N δ ,N ε -dimethylated histidinium oligopeptides Boc-Ala nHis*-OMe 4a (n = 2) and 4b (n = 3).…”
Section: Synthesis Of Alanine-based Histidylidene Metal Complexesmentioning
confidence: 99%
“…12 An alanine dipeptide linker was placed between the coordination sites in order to promote the formation of an α-helix. 21 Since a complete turn in a peptidic α-helix contains 3.6 amino acid 25 residues, the resulting tetrapeptides may adopt a conformation that is suitable for chelation where the side chain of the i+3 residue (i.e. Met/Tyr) is positioned almost eclipsed to the metalbound histidylidene unit.…”
Section: Synthesis Of Histidylidene Complexes Containing a Remote Potmentioning
confidence: 99%
See 1 more Smart Citation
“…17 It has been shown that for some repeating-sequence peptides, containing mainly alanine residues, the presence of TFE strengthens hydrogen bonds within the helical state to an extent sufficient to account for the increase in helix propensity in the presence of TFE. 18 An indirect mechanism may be involved in which peptide hydrogen bonds to the solvent are weakened in conjunction with lowering of the solvent dielectric constant. 19-21,1 Alternatively, helicogenic enhancement may occur by a direct mechanism involving preferential solvation of the polypeptide and direct binding of TFE to the polypeptide chain in the so-called helical state.…”
Section: Introductionmentioning
confidence: 99%